2020
DOI: 10.3390/ijerph18010206
|View full text |Cite
|
Sign up to set email alerts
|

Histological and Radiological Features of a Four-Phase Injectable Synthetic Bone Graft in Guided Bone Regeneration: A Case Report

Abstract: Background and objective: Injectable synthetic bone grafts (ISBG) are widely used biomaterials for regeneration purposes. The aim of this case report was to examine the efficacy of ISBG in the management of buccal fenestration in the case of a 25-year-old female. Case report: After a traumatic tooth extraction, the defect was filled with ISBG and covered with a resorbable membrane. The ISBG showed easy handling and the patient had no complications during healing. Six months after augmentation, a bone biopsy wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…Pathohistological analysis of the bone biopsies showed that the biomaterial in both groups was fully integrated into the surrounding tissue and was in close contact with the newly formed bone. These observations are identical to those previously described in human histological studies in which various bone defects were augmented with BX [ 42 , 43 ] or I-BCP [ 23 , 24 , 25 ]. Close contact between the residual biomaterial and the newly formed bone was observed in the biopsies of both groups, suggesting the osteoconductive properties of the biomaterial [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Pathohistological analysis of the bone biopsies showed that the biomaterial in both groups was fully integrated into the surrounding tissue and was in close contact with the newly formed bone. These observations are identical to those previously described in human histological studies in which various bone defects were augmented with BX [ 42 , 43 ] or I-BCP [ 23 , 24 , 25 ]. Close contact between the residual biomaterial and the newly formed bone was observed in the biopsies of both groups, suggesting the osteoconductive properties of the biomaterial [ 44 ].…”
Section: Discussionsupporting
confidence: 89%
“…Injectable biphasic calcium phosphate (I-BCP) showed good results in augmentation of three-dimensional cavities such as the maxillary sinus, extraction wounds or intrabony periodontal defects [ 22 , 23 , 24 , 25 , 26 ]. It is characterized by its viscosity, which allows more complete and easier filling of the bone defects.…”
Section: Introductionmentioning
confidence: 99%
“…Papanchev et al [ 31 ] published a case report comparing the percentage of new bone formation at two healing time points after sinus floor augmentation. Our group of authors has previously published a case report on the histologic and radiologic results of a four-phase injectable synthetic bone graft in GBR [ 32 ]. An extensive literature search revealed that no randomization clinical trial to date has evaluated the use of IBCP, composed of water-based gel with nano-hydroxyapatite particles and biphasic granules (60% HA and 40% β-TCP) for the indication of alveolar ridge preservation according to GBR principles.…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Khaled et al and Georgiev et al [ 51 , 52 ] using injectable biomaterials in combination with HA nanoparticles suggested that HA in the form of smaller granules contributes to better cellular interaction, leading to faster resorption of the biomaterial and promotion of new bone. We saw this ourselves when we used an injectable biomaterial with the addition of HA in a previous study [ 53 ]. Histomorphological and CBCT analyses showed that the granules integrate and are gradually replaced by newly formed bone.…”
Section: Discussionmentioning
confidence: 99%